Youth Football Players’ Psychological Well-Being: The Key Role of Relationships - Reverberi, Eleonora; D’Angelo, Chiara; Littlewood, Martin A.; Gozzoli, Caterina Francesca (Frontiers in Psychology, 2020)
Well-being in youth sport is a growing topic in literature. Practicing sports at a youth level is recognized as an important opportunity for growth and development but also an experience that conversely can prove to be tiring and cause discomfort. Sometimes expectations and pressures make it a risky experience. This is emphasized even more when looking at very popular and spectacular sports, such as football in some European Countries; practicing football often solicits the hope of becoming champions one day and thus being able living thanks to the beloved sport. How do young Italian football practitioners feel? What role do relationships with significant others belonging to the world of sport and extra-sport play on the well-being of young athletes? On which specific aspects of psychological well-being (PWB) are these relationships based? Are there any differences between elite and amateurs levels? These are the questions upon which this paper focuses, considering a sample of young Italian football practitioners. Analysis reveals a strong and positive influence of some dimensions of the relationships with significant others on PWB, specifically team effort, coach closeness, and parental learning climate. Moreover, elite players perceive significantly better relationships than sub-elite and amateurs and have significantly higher levels of PWB. Those results provide a first evidence for the importance of good relationships within and outside sport for an effective development of youth football players since they positively influence players’ PWB, which is higher in elite players. It emerges the necessity to further investigate different aspects of PWB and to deepen the knowledge about the meaning of relationship in developmental athletes according to a psychosocial approach.